The Psycholinguistics Approach: Contributions to English Language Pedagogy - Kaharuddin Kaharuddin (Jurnal Multidisiplin West Science, 2024)
Psycholinguistics is a study which explains how a person acquires, produces, and perceives language both orally and in writing. Moreover, psycholinguistics is a branch of cognitive science and one of the issues that has become a trending topic in cognitive science is the mind and its role in language use and acquisition. By understanding psycholinguistics, at least we know what processes occur in the mind related to language acquisition, what problems are experienced by a person's mind in the process of language acquisition. Of course, these types of information will provide many contributions for language teachers as well as curriculum and teaching material designers in streamlining the language teaching process, especially foreign languages. Contribution in this context refers to everything that psycholinguistics has provided and has been the cause of improvement or progress in the area of language pedagogy (learning and teaching).  To find out what these contributions are, the author has conducted a literature review by reading a variety of published opinions from psycholinguistic experts. At least, two types of contributions can be identified, namely theoretical contributions and practical contributions. Corley, K. G., & Gioia, D. A. (2011) refer to these two types of contributions as ‘scientific utility’ and ‘practical utility’.